2017
DOI: 10.1063/1.4976894
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances on Zeolite modification for direct alcohol fuel cells (DAFCs)

Abstract: Abstract. The increase of energy demand and global warming issues has driven studies of alternative energy sources. The polymer electrolyte membrane fuel cell (PEMFC) can be an alternative energy source by (partially) replacing the use of fossil fuel which is in line with the green technology concept. However, the usage of hydrogen as a fuel has several disadvantages mainly transportation and storage related to its safety aspects. Recently, alcohol has gained attention as an energy source for fuel cell applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Moreover, the performance of the zeolite composite membranes depends on the zeolite properties in terms of pore size and surface tension (hydrophobility or hydropholicity). It was reported that hydrophobic zeolites ensure low affinity to water so high permeability to methanol however hydrophilic zeolites lead to an opposite trend and therefore reduce methanol crossover [94]. When zeolites are combined with a polymer support (e.g., Nafion), the advantages of both polymer and zeolite are combined.…”
Section: Inorganic Fillersmentioning
confidence: 99%
“…Moreover, the performance of the zeolite composite membranes depends on the zeolite properties in terms of pore size and surface tension (hydrophobility or hydropholicity). It was reported that hydrophobic zeolites ensure low affinity to water so high permeability to methanol however hydrophilic zeolites lead to an opposite trend and therefore reduce methanol crossover [94]. When zeolites are combined with a polymer support (e.g., Nafion), the advantages of both polymer and zeolite are combined.…”
Section: Inorganic Fillersmentioning
confidence: 99%
“…Other electrochemical applications of dialysis are associated with electricity generation in newly designed fuel cells [49][50][51]. Although there are still far from practical applications, the research efforts deserve encouragement.…”
Section: Fuel Cell Applicationsmentioning
confidence: 99%
“…The isolation of carbon steel surfaces from corrosion agents is an effective strategy to prevent electrochemical corrosion [4,8]. Among several corrosion prevention methods commonly used, the use of corrosion inhibitor is an effective method and the most appropriate way to prevent corrosion [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the recent focus of research is to make environmentally friendly corrosion inhibitors, which have a low environmental risk. The use of an organic compound is one of the best candidates as a raw material to make environmentally friendly corrosion inhibitors [4,[6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation